Mobile application for intelligent transportation systems with vehicular communications integration - Teixeira, Gil Lopes (2024)
The exponential growth of the population and, consequently, of the amount of road users and vehicles has significantly impacted traffic congestion and road safety. Road accidents are responsible for the death of around 1.2 million people worldwide every year, but many could have been avoided. Intelligent Transportation Systems attempt to mitigate these problems by integrating a vast array of sensor data collection and processing techniques that provide real-time information to road users and traffic managers. Vehicular communications are a key component of these systems, as they allow vehicles to communicate with each other and with the road infrastructure to obtain contextually relevant information. This dissertation presents the development of a multi-platform mobile application designed to interface with either vehicles or a central information broker, facilitating monitoring and interaction within the ITS environment. The application integrates sensor data collection and sharing and can be used to create and visualize events that warn users of potential hazards, such as accidents, traffic jams, road works and adverse weather conditions in real-time, which can help prevent accidents and reduce congestion. Usability evaluations identified potential effectiveness challenges among older populations and unfamiliar technical terms for regular users, while performance evaluations revealed issues with real-time data processing and scalability, leading to device throttling. Insights from these evaluations informed improvements to the application and provided direction for future work, contributing to ongoing efforts to enhance road safety and alleviate congestion through the advancement of intelligent transportation systems and vehicular communication technologies.